Can digital cash transfers serve those in active conflict? Randomized intervention in Sudan - Abay, Kibrom A.; Siddig, Khalid (AEA RCT Registry, 2025)
This project evaluates the impact of digital transfer on well-being of households grappling with active conflict in Sudan. The case of Sudan offers an interesting setting where active conflicts and funding gap continues to hamper the delivery of humanitarian services. We aim to address the following questions: (1) Can digital cash transfers improve food and nutrition security outcomes of beneficiaries in conflict-affected settings? (ii) Can digital transfer to an otherwise inaccessible population improve subjective well-being, mental health, and stress in the face of recurrent conflicts? (iii) Do welfare impacts of digital transfers vary by the size of transfers or socioeconomic characteristics of households? (iv) Can digital transfers cushion the adverse impact of armed conflict on mental health? To address these questions, we design a Randomized Controlled Trial (RCT) involving digital transfer of different sizes to randomly selected urban residents in Sudan.